2018
DOI: 10.1063/1.5065541
|View full text |Cite
|
Sign up to set email alerts
|

Improving measurement accuracy of Brazilian tensile strength of rock by digital image correlation

Abstract: Since the invention of the Brazilian test about eight decades ago, discussions on the validity of indirect tensile strength measurement by the Brazilian test have always been of focus in rock fracture mechanics. According to the principles of the Brazilian test, experimental data are only valid when a fracture is initiated at/near the disc-shaped planar center and propagates along the diametral loading plane. However, traditional experimental results can only show readers a final failure instead of fracture pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…On the other hand, non-contact measurement techniques, such as Digital Image Correlation (DIC) in combination with high-speed photography are a promising tool to verify the validity of the Brazilian test. [35][36][37][38][39][40] Moreover, high-speed cameras are the most convenient way to capture the failure process. 41 However, some authors 36 concluded that even with high acquisition frequency systems, it is difficult to observe and identify the crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, non-contact measurement techniques, such as Digital Image Correlation (DIC) in combination with high-speed photography are a promising tool to verify the validity of the Brazilian test. [35][36][37][38][39][40] Moreover, high-speed cameras are the most convenient way to capture the failure process. 41 However, some authors 36 concluded that even with high acquisition frequency systems, it is difficult to observe and identify the crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In this process, transferred with the fracturing fluid, those solid proppants play an essential role in holding the fracture open and providing a high fracture conductivity, thus leading to an economic hydrocarbon extraction from the fractured unconventional pay zones. [1][2][3][4] In this process, transferred with the fracturing fluid, those solid proppants play an essential role in holding the fracture open and providing a high fracture conductivity, thus leading to an economic hydrocarbon extraction from the fractured unconventional pay zones.…”
Section: Introductionmentioning
confidence: 99%
“…To successfully stimulate the productivity of the lowpermeability unconventional reservoirs (eg, tight oil sandstones and gas shale reservoirs), hydraulic fracturing has been widely used to create tiny fractures and connect natural fractures by injecting highly pressurized fracturing fluid. [1][2][3][4] In this process, transferred with the fracturing fluid, those solid proppants play an essential role in holding the fracture open and providing a high fracture conductivity, thus leading to an economic hydrocarbon extraction from the fractured unconventional pay zones. [5][6][7] The proppant should have a high resistance to the fracture closure stress after decreasing the fracturing pressure, in case that they would be crushed under a tremendous value of loading.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect approaches such as the Brazilian disc test are widely utilised by researchers due to their simplicity and efficiency during sample preparation and testing procedures [3]. Valid tensile pattern Brazilian disc of rock specimens can also be visualised through digital image correlation [4]. Several tests such as the half-ring and semi-circular bending tests are relevant to determine the TS of brittle rocks [5,6].…”
Section: Introductionmentioning
confidence: 99%